Kravtsov А.G. Modeling the formation of an oil film on the surface in the presence of fullerene additives in a lubricant and its effect on the wear rate of tribosystems. - Кравцов, А. Г. (Problems of Tribology, 2018)
The simulation of the formation of an oil film on the friction surface in the presence of solutions of fullerenes in a lubricant and their effect on the wear rate of tribosystems are presents in the paper. Based on the simulation results, it is established that the magnitude of the electrostatic field strength of the friction surface is a more significant factor in the formation of the thickness of the oil film on the friction surface than the electric field of the lubricant. Rational concentrations of fullerenes and vegetable oil as additives in base lubricants have been established, which will reduce the volumetric wear rate of tribosystems.